Development and performance test of UWB radar life detector for mine borehole rescue - Xi CHEN; Hu WEN; Yuan HUANG (Meikuang Anquan)
In response to the problem of blocked escape routes and difficulty in determining the location of trapped personnel caused by mining disasters and accidents, based on the principles and characteristics of ultra wideband (UWB) radar life information detection and position detection, combined with existing UWB radar detection technology, a UWB radar architecture suitable for borehole detection is proposed, key technical parameters are clarified, and a UWB radar life information detector is developed; we conducted UWB radar detection experiments under different detection distances, positions, target numbers, and weak body movements, and obtained detection spectrum features under three conditions. The experimental results show that the UWB radar life information detector can penetrate a 0.5 m brick wall and accurately locate personnel spatial information in complex terrain after disaster deformation. It can observe small-scale movements of personnel within a range of 4.0 m from radar echoes; when multiple human targets are within the same range of the radar transmitting and receiving antennas, and there are differences in their radial relative positions from the radar, the number of human targets can be determined based on the echo spectrum.